Exploring the link between social participation, functional health, and depression among older adults - Raman Mishra; Dil Bahadur Rahut; Raja Rajendra Timilsina; Tetsushi Sonobe (Asian Development Bank Institute (ADBI), 2024)
The growing number of older adults due to the demographic transition has brought about a complex change in health and disease patterns. Depression is common among older adults, linked to cognitive impairment and reduced physical activity. Little is known about the relationship between social participation, functional health, and depression in the older adult population. Therefore, this study used data from the WHO-SAGE Wave 2 (2015) survey and analyzed a sample of 7,118 older adult respondents from India aged 50 and above. The results revealed that considering functional health (WHODAS) as a mediator, it is evident that with improving functional health and a high level of access to social participation, depression among older adults is reduced. High levels of social participation and improved functional health are associated with a lower risk of depression among older adults. The study also found that older adults residing in rural areas and those that are divorced, separated, or widowed are at a higher risk of depression. Additionally, tobacco consumption is positively associated with the risk of depression among older adults. These findings emphasize the importance of social participation and functional health in reducing the risk of depression among older adults. The study suggests that physical activity and social capital are crucial for successful aging. The study recommends that older adults should engage in physical activity and participate in structured programs supported by peer groups and community participation. Living in a society with strong social networks and a supportive environment can also reduce the risk of depression among older adults.
Keywords: J14; I12; I18; I10; 330; social participation; functional health; mental health; older adults; India